The senses - Kittredge, Mary, 1949- (New York : Chelsea House, 1990)
Discusses the five senses, the structure and function of the sensory organs, their interrelationship with the brain and nervous system, and dysfunctions and problems of the senses.
Includes bibliographical references.
Wilson's Junior High School.
7.5
4-6
Young Adult
Keywords: Senses and sensation -- Juvenile literature; Senses and sensation; Senses and sensation